2000
DOI: 10.1074/jbc.c000411200
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate Is Not a Messenger in Insulin Secretion

Abstract: Experiments do not support a recent claim that glutamate formed from the amination of citric acid cyclederived ␣-ketoglutarate is a messenger in glucose-induced insulin secretion (Maechler, P., and Wollheim, C. (1999) Nature 402, 685-689). Glucose, leucine, succinic acid methyl ester, and ␣-ketoisocaproic acid all markedly stimulate insulin release but do not increase glutamate levels in pancreatic islets. Increasing the intracellular glutamate levels to 10-fold higher than basal levels by adding glutamine to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
136
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(156 citation statements)
references
References 25 publications
17
136
3
Order By: Relevance
“…Overexpression of glutamate decarboxylase, resulting in increased production of GABA, inhibits insulin secretion in a rat model (63). The substrate for this reaction, glutamate, has been proposed to act as a coupling factor in GSIS (64), although its importance is controversial (65). Independent of the potential role for glutamate as a coupling factor, glutamate and aspartate are important intermediates in the malate-aspartate shuttle.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of glutamate decarboxylase, resulting in increased production of GABA, inhibits insulin secretion in a rat model (63). The substrate for this reaction, glutamate, has been proposed to act as a coupling factor in GSIS (64), although its importance is controversial (65). Independent of the potential role for glutamate as a coupling factor, glutamate and aspartate are important intermediates in the malate-aspartate shuttle.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies in several laboratories have failed to identify increases in glutamate levels during glucose stimulation of ␤-cells (8,9,40). Moreover, glutamate probably serves as an insulin secretagogue via glutaminolysis or oxidation of glutamate in the TCA cycle (41).…”
Section: Discussionmentioning
confidence: 99%
“…However, the kinetics of insulin release and of proinsulin biosynthesis, and the metabolic signals mediating these processes, are not identical [3,8]. In fact, the role of various glycolytic and TCA cycle intermediates in glucose-stimulated insulin secretion is controversial [7,[9][10][11][12][13][14][15][16], and even less is known about the metabolic signals for glucose-stimulated insulin production. A previous report by Alarcon et al suggested that succinate is the key signal for glucose stimulation of preproinsulin mRNA translation [3].…”
Section: Introductionmentioning
confidence: 99%